Analysis of Olfaction after Bilateral Nasoseptal Rescue Flap Transsphenoidal Approach with Olfactory Mucosal Preservation. (November 2019) - Griffiths, Chester F.; Barkhoudarian, Garni; Cutler, Aaron; Duong, Huy T.; Karimi, Kian; Doyle, Olivia; Carrau, Ricardo; Kelly, Daniel F.
Objective: To ascertain the impact of septal olfactory strip preservation and bilateral rescue flap elevation on the incidence of olfactory dysfunction. Study Design: Case series with chart review of patients undergoing endoscopic endonasal skull base surgery (2012-2014). Setting: Providence Saint John's Health Center and John Wayne Cancer Institute. Subjects and Methods: The incidences of postoperative epistaxis, hyposmia, and anosmia were analyzed using the Brief Smell Identification Test (B-SIT), which was completed in 110 of the 165 patients. Results: Seventy-eight patients required extended approaches. Bilateral nasoseptal rescue flaps were elevated in 144 patients (87.3%) and pedicled nasoseptal or middle turbinate flaps in 21 patients (12.7%). The neurovascular pedicles were preserved in all patients, and there were no episodes of postoperative arterial epistaxis. Normal olfaction was noted in 95 patients (86%), with new hyposmia noted in 5 patients (5.5%). Within the rescue flap cohort, new hyposmia occurred in 6.3% ( P < .01) of patients, balanced by improvement of olfaction in 43% of patients with preoperative dysfunction (overall pre- and postoperative olfactory function: 85% vs 86%). Patients with pedicled nasoseptal flaps did not have new hyposmia, with a net improvement of olfaction (71% vs 86%, P = .07). No patients experienced new anosmia. There was no difference between flap type within either subgroup. Conclusions: Superior olfactory strip preservation during elevation of reconstructive flaps preserves olfactory function and maintains adequate surgical exposure. In addition, rescue flaps have significantly diminished the rate of arterial postoperative epistaxis while maintaining the ability to harvest nasoseptal flaps for future reconstruction.